Holistic Management of Pediatric Patients with Asthma through the Family Medicine Approach: A Case Series - Azwin Mengindra Putera; Dinda Sella Octaviana; Fanny Gunawan; Manika Putri Kunigara; Junjungan Nimasratu Rahmatsani; Lavenia Kurniawati; Ferrel Bramasta; Istianah Istianah; Jihan Nabila Pranjasdhina; Gerald Sebastian Davis; Ashfa Diniyya Assabella; Akbar Rizky Ramadhan; Veronika Intan Krismaningrum; Wigaviola Socha Purnamaasri Harmadha (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Asthma is a global problem, with around 100-150 million people estimated to suffer from this disease. Based on data from the Centers for Disease Control and Prevention (CDC), around 8.4% of people in the United States suffer from asthma. Asthma requires holistic treatment, one of which is family medicine. However, there is a lack of data or research discussing this matter. Hence, this case report aims to provide an overview of family medicine in asthma, especially in children. Case: This study is a case series report involving four pediatric patients with asthma. Data collection was performed by conducting home visits and hetero-anamnesis. Many things affect asthma treatment apart from pharmacology, including family medicine. In this case series, the role of the family proved significant in the patient's healing and daily functioning. Conclusion: Family medicine is a type of holistic management critical in various diseases, especially asthma. Support from the patient's family and environment has an essential role in the success of asthma therapy in children.